Exposure to Violence, Firearm Involvement, and Socioemotional Consequences Among California Adults - Aubel, Amanda J. (Journal of interpersonal violence, 2021)
Violence is a leading cause of injury and death, and its impacts extend far beyond physical harm to the victim. We estimated the prevalence of direct or indirect exposure to violence, factors associated with exposure, and effects of exposure on socioemotional health—with effect modification by firearm involvement during the violent event—among a state-representative sample of California adults. We also examined effects of exposure on subsequent intent to purchase firearms. The sample comprised 2,558 California adults who completed the 2018 California Safety and Wellbeing Survey. An estimated 4% of respondents—1.2 million Californians—said they or a household member were exposed to violence while living in their current neighborhood. Half of those exposed to violence reported the event was “severely” distressing, and 47% experienced social functioning problems (i.e., problems with job/school and/or family/friends); for comparison, only 12% of unexposed adults reported having such problems in the past 12 months. When the violent event involved a weapon, respondents who did (versus did not) experience severe distress were significantly more likely to report that a firearm was present (69% versus 14%); those with (versus without) social functioning problems were significantly more likely to report other types of weapons were involved (67% versus 22%). Exposed adults considered buying a gun in response to the violent event more often than did unexposed respondents in the past 12 months (33% versus 17%). These findings highlight the need to address the physical and psychological sequelae of violence exposure among direct and indirect victims and can inform violence prevention research, programs, and policies across the nation.